Universal and Selective Housing Regimes as Broad and Narrow Policy Fields. A Conceptual Proposal and its Application to Sweden - Bo Bengtsson; Martin Grander (Tidsskrift for boligforskning)
A fundamental distinction in welfare state research is the one between universal and selective policies. Consequently, housing researchers often categorize national housing regimes under one of these headings. However, since housing is typically distributed via markets – although with state correctives – and not directly by means of state distribution, the borderline between universal and selective housing policies is seldom clear-cut. This article proposes a framework that can be applied both to housing and other welfare sectors, based on the distinction between a broad and narrow policy field and applicable to institutions, discourses and outcomes on different political levels: national welfare regimes, sector regimes (like housing) and policy instruments. In the article, this framework is applied critically to the Swedish housing regime, which is often understood as being universal. Swedish housing policy and its central policy instruments are analysed in terms of universality and selectivity, together with the housing discourse and the social and economic outcome. The article also discusses how the development of recent years, for example, the increased commercialism of public housing, the spread of so-called social contracts and the recurring ideas about “social housing” can be understood in terms of universal and selective housing policy.